Stosunek prawny a relacja prawna - Patryas, Wojciech (PRAWO i WIĘŹ, 2025)
A legal relationship can be understood in this or that way, but it must be based on a legal norm. However, rules are interpretable, and both norms and propositions constitute objects. In contrast to a legal relationship based on a legal norm, a proposition constituting an object is based on a legal connection.